Targeting EZH2 reactivates a breast cancer subtype-specific anti-metastatic transcriptional program - Alison Hirukawa (Nature Portfolio, 2018)
Histone modifications in cancer can contribute to pathogenesis. Here, the authors demonstrate that targeting epigenetic modifier Ezh2 hinders metastatic behaviour in Luminal B breast cancer models, and highlight a mechanism where Ezh2 contributes to metastatic behaviour by repression of FOXC1.